Governance Network Theory: Towards a Second Generation: with the introduction of Bob Jessop - Torfing, Jacob (Journal of Public Governance, 2011)
Governance networks have increasingly gained prominence in the wake of the many reports of government and market failure. Drawing on the burgeoning literature, we first define governance networks and then briefly assess their merits and shortcomings. The key hypothesis is that we are now seeing the development of a second generation of governance network research that focuses on new and yet unanswered questions about the prospects of networkbased coordination across different levels of governance: the meta-governance of self-regulating networks, the role of discourse in relation to governance networks, and the democratic problems and potentials of network governance. In answering these important questions, we can draw on different theoretical approaches to network governance, and these are briefly delineated.